Epstein-Barr virus DNA is amplified in transformed lymphocytes. - Sugden, B (1979)
Leukocytes isolated from two adult donors who lacked detectable antibodies to antigens associated with Epstein-Barr virus were exposed to an average of 0.02 to 0.1 DNA-containing particles of Epstein-Barr virus per cell and immediately clones in agarose. Within about 30 generations all transformed cell clones contained between 5 and 800 copies of viral DNA per cell. Only 1 in 10(4) to less than 1 in 10(5) of the cells of each clone release virus, and the frequency of release did not correlate with the average number of copies of viral DNA in the cells of each clone. One clone that had an average of five copies of viral DNA per cell was recloned, and the average number of copies in four of six subclones increased 15-to 50-fold while the subclones were being propagated sufficiently to study them. These results indicate that Epstein-Barr virus DNA can undergo amplification relative to cell DNA at different times after it transforms cells.